Determination Of Bukit Merah Reservoir Capacity Using Sequential Peak Analysis - Azhani, Aidatul Aznuraini Aidil (Universiti Sains Malaysia, 2022)
Bukit Merah Lake or Bukit Merah Reservoir is the first man-made lake in Malaysia located in the north of Perak which was built in 1906. Since the structure of the dam is aging, it would affect its effective function and some of the problems introduced regarding storage capacity. For this case study, determination of Bukit Merah Reservoir storage capacity is the crucial step for preserving its water storage which influenced all the essential basic things such as irrigation, domestic and flood mitigation. A sequent peak algorithm is a technique designed primarily to estimate the size of active storage by tracking the inflows and outflows over an interval. It is the minimum storage capacity which is required for a reservoir to have been equal to the maximum of the deficit that occurs in a strict during a given period. The Sequent Peak Analysis is chosen because it is easy to program, suits with large data and considers evaporation losses compared to other methods which is Mass Curve Method. The reservoir is assumed to be full during the beginning of dry period. In addition, the issue of illegal encroachment and exploration activities led to reducing of storage capacity as sedimentation accumulated due to excess runoff. High rate of evaporation also contribute to this problem as there was El-Nino phenomenon occur in year 2016. It was concluded that Bukit Merah Reservoir is insufficient to accommodate irrigation and domestic supply as well as flood mitigation. The current water demand is high release compared to its capacity (92.8 MCM). Determining reservoir capacity is an important part of water resources development projects and sustains the needs in such a long-term period.